The Geomorphological Factors and Its Implications for The Tidal Energy Installations in Java, Indonesia - Fahmi Arif Kurnianto; Fahrudi Ahwan Ikhsan; Bejo Apriyanto; Elan Artono Nurdin; Tyas Nisa Fadilah (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
This study aims to place the tidal energy installation effectively in Indonesia based on geomorphological factors. The survey method was used to analyze the characteristics of beaches in Indonesia. Mathematical physics model was implemented to find the new formulas based on geomorphological factors. Tides are the result of gravitational attraction and the centrifugal effect, which is the drive In the earth-moon system, tidal generating forces are the resultant forces that cause tides, namely: the earth-moon system (FS) centrifugal force and the moon's gravitational force (FB). FS works in the center of the mass of the earth-moon system whose mass point is located on the 3/4 radius of the earth. The style of tidal generator caused by the moon can be calculated by combining Newton's universal gravitational law .The results of this study consist of F = m ac, where the style of the tidal generator caused by the moon can be calculated by combining newton's universal gravitational law in equation and newton's second law of motion in Equation. The another results is tan = , where the formula takes into account constants (K) based on slopes. The last result is the constants (K) for each land form starting on 0,00 untill 1,00. The north coast of Java is more suitable for tidal energy installations because the land form is dominated by alluvium plains of the quaternary age with a lower risk than the southern region of Java. The effectiveness of tidal energy installation depends on the characteristics of the land form. In alluvial plains, the quaternary age of the alluvial plains is more suitable than the hill form volcanic quaternary, tertiary volcanic, and tertiary holokarst.